Analisa Gaya dan Koefisien Gesek Ban Berdasarkan Perbedaan Massa Mobil Terhadap Permukaan Jalan Aspal - Pasaribu, Muhamamd Nuh Hudawi (CV. IRA PUBLISHING, 2024)
In general, roads consist of asphalt road surfaces and concrete road surfaces which have different surface textures. Of the two roads, asphalt roads are generally longer or more frequently traveled than concrete roads. Asphalt roads have a smooth rough texture. The texture of road surface roughness (IRI) will have an impact on safety and comfort such as the friction coefficient of vehicle tires when passing over rough road surfaces. Safety and comfort are influenced by IRI, mass, speed and type of tire used when in contact with the road surface texture. The aim of this research is to obtain the IRI value using the Naasra Roughness meter ARRB, to obtain the magnitude of the force and coefficient of friction applied on the Abdul Haris Nasution road Medan which has an asphalt road length of 3200 meters with an experimental method using a 2010 Toyota Yaris at a speed of 10 km/hour to 45 km/hour. From the results of experimental research, an IRI value of 6.4 was obtained. The faster the vehicle/car passes, the smaller the force value and friction coefficient value can be at an initial speed of 10 km/hour.